The homily as a way to the synodal Church.The possibility of building a responsible laity - Janez Vodičar (Polonia Sacra)
The first Church was formed during the Pentecostal speech of the apostles. The first forms of evangelization were narratives of personal experiences with Jesus. With the formation of structures in the Church, the role of authority in official proclamation in worship also developed. We will try to show how a communal sharing of God's word is necessary for a communal participation in Christ's sacrifice on the way to synodality. Pope Francis encourages everyone to bear witness to Christ. We would follow the words that Pope Francis wrote in The Joy of the Gospel: “We are not asked to be flawless, but to keep growing and wanting to grow as we advance along the path of the Gospel; our arms must never grow slack.” The fear of losing touch with the sources of Revelation and from the diversity of faith experiences must not stop us from seeking a word that would, as at the first Pentecost, inspire people to live the gospel. The primary responsibility for more believers to participate in the sacrifice of the Word in our liturgy lies with those who can speak today. We will point out guidelines on how to educate for greater participation and open the possibility for institutional change through the homily as we know it today. We will also point out some good practices that reflect the possibility of education for the testimony of all believers needed for a synodal Church.